Applicability of the induction bending process to the P91 pipe of the PGSFR - Kim, Nak Hyun; Kim, Jong Bum; Kim, Sung Kyun (Nuclear engineering and technology, 2021)
The application of induction bending processes to industrial pipe production is increasing. The induction bending process has the effect of reducing the number of inspections and preventing leaks by reducing the weld of the pipe. For these reasons, efforts have been made to apply an induction bending process to the pipe of the PGSFR under development in Korea and this is the first attempt in the SFR design. Since the PGSFR pipe has a relatively large diameter-to-thickness ratio, it is difficult to fabricate an induction bending pipe that meets the requirements. In addition, the material properties may change because the pipe heats to a very high temperature during the induction bending process. In this study, P91 pipes were fabricated by induction bending, and the results from analyzing the induction bending process’ applicability to the P91 pipe of the PGSFR are examined. The various dimensional measurements of the pipes fabricated by the induction bending process were surveyed to determine whether the requirements of the ASME Code were met. The minimum thickness, ovality, and wall buckling measured in the fabricated pipe met all the requirements. Tensile, impact, and hardness tests at various locations of the fabricated pipe also satisfied the requirements.